Evidence-Based Design of University Zoological Gardens: A Perception Study in South-west Nigeria (2018)
Evidence-based design (EBD) has become an acceptable paradigm in environmentbehaviour endeavours in recent years with documented benefits especially in healthcare facilities. However, little is known of its application to University Campus Open Spaces (UCOS) like University Zoological Gardens (UZGs) which accounts for the repetition of design mistakes. This study aims to assess the UZGs as a major component of UCOS in South-west Nigeria with a view to formulating EBD frameworks. It adopts a comparative post-occupancy evaluation (POE) approach through a Stratified Random Sampling protocol of users (n=3,016) of the gardens in Federal Universities in South-west Nigeria. Results of the quantitative data analyses suggest that while walk-ability is a primary satisfaction factor among thirty design considerations in the formulated model, legibility is the most primary cognitive factor for designing perceptible high quality UZGs. The study argues in favour of the developed framework as design tool-kit and recommends its application as a feedback input into the design process of UZGs